Survival and transmission of Xanthomonas oryzae pv. oryzae in rice seeds - Mondal, Sony; Hossien, Md Emran; Akter, Mst Arjina; Haque, Md Mahbubul; Ali, Md Ayub; Islam, Md Rashidul (Fundamental and Applied Agriculture, 2018)
Xanthomonas oryzae pv. oryzae is a major pathogen of rice that causes bacterial leaf blight (BLB) disease and is a great threat to rice production worldwide. Transmission of X. oryzae pv. oryzae from seed to seed is remain in enigma. In this study, seed transmission was investigated to detect and identified X. oryzae pv. oryzae in rice seeds of BR11 collected from the naturally BLB infected field and the transmission of X. oryzae pv. oryzae from seed to plant to seed during November, 2014 to November, 2015 at Seed Pathology Centre, Bangladesh Agricultural University, Mymensingh. The results indicated the survival ability of X. oryzae pv. oryzae for one season to another for at least 10 months but the survivability of the bacterium decreased with the increasing of storage time. The transmission of X. oryzae pv. oryzae was carried out through transplanting of the seedlings raised from the infected seeds. X. oryzae pv. oryzae was then detected in the seeds harvested from the infected plants raised from the seedlings produced from the previously harvested BLB infected seeds. These results clearly indicated the transmission of X. oryzae pv. oryzae from seed to plant to seed carryover at least from one season to another. Keywords: Seed, transmission, rice, bacterial leaf blight